2013
DOI: 10.1007/s12178-013-9188-5
|View full text |Cite
|
Sign up to set email alerts
|

Complications of total hip arthroplasty: periprosthetic fractures of the acetabulum

Abstract: Periprosthetic fractures of the acetabulum are a rare but potentially disastrous complication of total hip arthroplasty. Such fractures occur either as early perioperative complications or late complications when they are associated with either significant trauma or as a result of the loss of the structural integrity of the bone supporting the prosthesis, such as aseptic osteolysis. The incidence of such fractures appears to be increasing with the increased use of uncemented acetabular components. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Major mistakes as femoral anterior notching in total knee replacement have been proven to be associated in 10-46% of cases with supracondylar fractures (17) even though some recent studies disproved that (3). Several studies reported higher rates of fractures after cementless implants and press-fit techniques (4,5,(18)(19)(20). A review carried out by Abdel et al point out that the femoral intra-operative fractures occur 14 times more often when a cementless stem is used for THA.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…Major mistakes as femoral anterior notching in total knee replacement have been proven to be associated in 10-46% of cases with supracondylar fractures (17) even though some recent studies disproved that (3). Several studies reported higher rates of fractures after cementless implants and press-fit techniques (4,5,(18)(19)(20). A review carried out by Abdel et al point out that the femoral intra-operative fractures occur 14 times more often when a cementless stem is used for THA.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…The latter method, underreaming and press-fit impaction of the component with or without additional screw fixation, has become the most popular fixation technique [11]. With this technique, recognizable intraoperative fractures of the acetabulum sometimes occur during impaction, but such fractures during primary arthroplasty are rare [6,7,12,23]. The rate of intraoperative fracture of the acetabulum during primary THA has been reported as 0.4% [12], whereas the rate of recognizable periprosthetic fractures of the femur with cementless femoral components in primary THA is generally less than 5% [3,17,21,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…As part of other study protocols that obtained preoperative and postoperative CT images on a large number of primary THAs for templating and computer navigation purposes [10,[14][15][16]18], we routinely recognized postoperative acetabular fractures on these images and thought that the incidence of these fractures was unexpectedly high. Previous reports have indicated that underreaming or oversizing the cup (insertion in rigid bone), osteoporosis, and a preoperative diagnosis of rheumatoid arthritis were risk factors for periprosthetic fractures of the acetabulum which were detected during surgery and with postoperative radiographs [6,7,14,20,30]. These fractures also occasionally are diagnosed when a patient reports groin pain during the weeks after surgery [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic discontinuity is the far end of bone loss for hip arthroplasty and it is described as separation of superior part of pelvis from inferior one. 19 The Vancouver classification divides periprosthetic femoral fractures into types A, B, and C according to localization; proximal, distal and below stem (Figure 4). Further categorizes type A into two subtypes (AG and AL) and type B fractures into three subtypes (B1, B2, and B3 according to bone quality and stem security).…”
Section: Infectionmentioning
confidence: 99%